Sistem Pengawasan Berbasis IoT pada Robot Vision Untuk Peningkatan Keamanan Perimeter di Industri Batam - Caniago, Deosa Putra; Muhammad Jufri; M Abrar Masril (The Indonesian Journal of Computer Science, 2024)
Batam City faces significant security challenges alongside rapid industrial growth, making the need for effective surveillance systems in industrial areas urgent. This research developed a surveillance robot utilizing Internet of Things and computer vision technologies to enhance perimeter security in industrial zones. The robot is equipped with Arduino as the controller, a Pixy2Cam camera for object detection, and a WiFi module for remote connectivity. Testing results indicate that the robot can detect individuals wearing safety gear in 0.2 seconds and achieves a detection success rate of 100% under ideal conditions. The developed controller application using MIT App Inventor also displays real-time images, allowing for rapid responses to potential threats. This research demonstrates that the developed surveillance robot effectively enhances monitoring in the Batam industrial area.